Kinerja Keuangan Bank Umum Syariah di Indonesia Pasca Pandemi COVID-19 - Annisa, Mutiara; Ridhani, Ridhani; Timoria, Timoria; Zulfa, Andria; Sakuntala, Dwita (Fakultas Ekonomi Universitas Samudra, 2024)
The aim of this research is to analyze the financial performance of sharia commercial banks (BUS) after the COVID-19 pandemic through the CAR, NPF, FDR and BOPO variables on the ROA of BUS registered with the OJK 2019-2024. The method used is quantitative with a research sample of 6 BUS determined through a purposive sampling technique. The secondary data analyzed was obtained through the official OJK website. The data is then analyzed through descriptive statistics, classical assumption tests, and hypothesis testing. The empirical findings show that all CAR, FDR and BOPO variables partially have no influence on ROA from BUS, except that NPF is proven to partially have a positive influence on ROA. Simultaneously, all independent variables have an influence on BUS ROA.